Histologic differentiation and mucin phenotype in white opaque substance-positive gastric neoplasias - Ueo, Tetsuya; Yonemasu, Hirotoshi; Yao, Kenshi; Ishida, Tetsuya; Togo, Kazumi; Yanai, Yuka; Fukuda, Masahide; Motomura, Mitsuteru; Narita, Ryoich; Murakami, Kazunari (Endoscopy International Open, 2015)
Background and study aims: The authors previously reported that the white opaque substance (WOS) in gastric epithelial neoplasia was caused by accumulation of lipid droplets by immunohistochemical and immunoelectron microscopic studies of adipophilin, which was recently identified and validated as a marker of lipid droplets. The aim of the current study was to investigate the characteristics of the histologic differentiation and mucin phenotype in WOS-positive gastric epithelial neoplasias.Patients and methods: A total of 130 gastric epithelial neoplasias (45 adenomas and 85 early adenocarcinomas) from 120 patients were retrospectively evaluated. The presence or absence of WOS was evaluated by M-NBI. Lipids were examined by immunohistochemical staining for adipophilin. Tissue phenotypes were immunohistochemically classified as intestinal (I), gastrointestinal (GI), and gastric (G) using antibodies against CD10, MUC2, MUC5AC and MUC6. The histologic differentiation and mucin phenotype of WOS-positive neoplasias were characterized and examined according to adipophilin expression.Results: The presence of WOS by M-NBI was correlated with histologic differences between adenoma or differentiated type adenocarcinoma and mixed type or undifferentiated type adenocarcinoma (P = 0.0153). Adipophilin was only expressed in primary adenoma and well to moderately differentiated adenocarcinoma components but not in undifferentiated components. WOS and adipophilin expression were only observed in neoplasias with I or GI phenotypes, but not in those with the G phenotype (P < 0.0001). Conclusions: WOS in gastric epithelial neoplasias might indicate differentiation into a mature histological subtype with GI or I mucin phenotype.